Review of the genus Paramanota Tuomikoski (Diptera, Mycetophilidae), with the description of new fossil and recent species - Hippa, Heikki (Zootaxa, 2010)
The genus Paramanota includes the following species: P. awanensis Hippa, Jaschhof & Vilkamaa (Peninsular Malaysia), P. bifalx sp. n. (Thailand), P. furcillata sp. n. (Thailand), P. grandaeva sp. n. (Baltic amber), P. orientalis Tuomikoski (Burma and Thailand), P. paxillosa sp. n. (Thailand), P. peninsulae Hippa, Jaschhof & Vilkamaa (Peninsular Malaysia), P. schachti Papp, and P. sumatrana Hippa, Jaschhof & Vilkamaa (Sumatra). P. orientalis is redescribed. A key to the species is given. Generic characters of Paramanota are discussed.